Evaluation of the MARPOL 73/78 Surveyor Training Course Towards its Enhancement - Sevilla II, Anthony T. (Future Science / FSH-PH Publications, 2024)
This thesis investigated the effectiveness of the MARPOL 73/78 Surveyor Training Course offered by Oceanwide Maritime Services Corp. and identified potential areas for enhancement. The study assessed course content, instructor qualifications, delivery methods, facilities, equipment, and learning assessment using Kirkpatrick's Model. It engaged 110 maritime professionals through structured questionnaires and client satisfaction surveys. Findings indicated that the course was highly effective in terms of content, instructor qualifications, and assessment methods while teaching materials and course duration received lower scores. Recommendations included updating course content, increasing hands-on training, upgrading facilities, diversifying delivery methods, enhancing assessment techniques, extending course duration, and providing support for complex topics. In conclusion, the MARPOL 73/78 Surveyor’s Training Course is highly effective but needs improvements in teaching materials, course segments, and regular content updates to maintain training quality and relevance.